Diagnostic Difficulties in Woman with Crohn’s Disease, Ascites, and Elevated Value of Serum CA125 Antigen - Maria Kłopocka; Ariel Liebert; Joanna Bielińska; Marcin Manerowski (Case Reports in Medicine)
Variety of symptoms and atypical clinical course of Crohn’s disease (CD) often create the need for additional diagnostic procedures. In the described case of woman with CD, there was a suspicion of coexistence of ovarian cancer. This issue is particularly important in patients treated with immunosuppressants and biological agents. The discussion focused on the usefulness of CA125 (cancer antigen 125, mucin 16) serum level estimation in clinical practice and draws attention to the possible reasons for the increase of its value which is not associated to ovarian cancer.